Morphoanatomy and Screening Metabolites Profile of Pararuellia napifera (Zoll.) Bremek. & Nann.-Bremek. (Gempur Batu) at Different Altitudes - Lestari, Sri; Aryani, Riska Desi; Amurwanto, Adi; Palupi, Dian (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Pararuellia napifera (Zoll.) Bremek. & Nann.-Bremek. (Gempur Batu) is a wild plant that can thrive in tropical areas and is traditionally used to treat nephrolithiasis. Therefore, this study aimed to explore the morphological, anatomical, and secondary metabolite profiles of P. napifera that grow at different altitudes. This study was conducted using a purposive sampling survey method in the lowlands (<400 m.a.s.l) and highlands (>800 m.a.s.l) in Banyumas, Central Java. The results show that P. napifera at both altitudes has a shrub habitus with fibrous roots, creeping round stems, alternated simple leaves, verticillaster compound flowers, and oval-shaped fruits (foliculus) with blackish-brown color flattened round seeds. P. napifera in lowland regions exhibit greater morphological characteristics compared to those in highland areas, with an average height of 18.5 cm in contrast to 12.64 cm. The habitus of P. napifera in lowland regions also indicates larger stem diameters and leaf sizes. Anatomical analysis of the roots stems, and leaves of P. napifera from both lowland and highland regions reveals a consistent tissue arrangement, although differences are observed in the structure of the transport tissues. Meanwhile, the result of phytochemical screening shows that the roots and leaves extracts contain flavonoids, alkaloids, terpenoids, tannins, and saponins.